Task influences pattern discriminability for faces and bodies in ventral occipitotemporal cortex. (1st November 2016) - Kim, Na Yeon; McCarthy, Gregory
ABSTRACT: Our prior research showed that faces and bodies activate overlapping regions of the ventral occipitotemporal cortex (VOTC). However, faces and bodies were nonetheless discriminable in these same overlapping regions when their spatial patterns of activity were classified using multivoxel pattern analysis (MVPA). Here we investigated whether these spatial patterns and their time courses were influenced by different categorization tasks. Participants viewed pictures of faces or headless bodies depicting a happy or fearful emotion. In one task, they categorized the picture as a face or a body regardless of emotion. In the other task, they categorized the emotion regardless of whether it was depicted by a face or body. Using a classifier trained on independent data, we found higher face–body classification accuracy for the emotion categorization task. The classifier was applied to each post-stimulus time-point to characterize the temporal course of classification. Accuracy initially rose equivalently above chance for both tasks, but then increased over a longer duration when participants categorized emotions. Thus, the temporal course of pattern differences between faces and bodies in VOTC was modulated by the behavioral goal of the observer, suggesting the top-down modulatory effect of task context on the category-selectivity activity in the VOTC.